2002
DOI: 10.4049/jimmunol.168.4.1649
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth Response Transcription Factors Are Required for Development of CD4−CD8− Thymocytes to the CD4+CD8+ Stage

Abstract: Progression of immature CD4−CD8− thymocytes beyond the β-selection checkpoint to the CD4+CD8+ stage requires activation of the pre-TCR complex; however, few of the DNA-binding proteins that serve as molecular effectors of those pre-TCR signals have been identified. We demonstrate in this study that members of the early growth response (Egr) family of transcription factors are critical effectors of the signals that promote this developmental transition. Specifically, the induction of three Egr family members (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 58 publications
4
99
0
2
Order By: Relevance
“…EGR1 was also represented by two probesets and the expression levels were significantly reduced after 16 h. This gene codes for a zinc-finger transcription factor. EGR proteins play central roles in controlling the differentiation program initiated by pre-TCR signalling [37,38] and in mature CD4 + T cells it was recently shown that EGR1 is required for CD154 (CD40 ligand) transcription [39]. The transcriptional regulators HEY1 and KLF10 are involved in regulation of cell fate decisions and proliferation, respectively, but have yet not been investigated in T lineage cells.…”
Section: Discussionmentioning
confidence: 99%
“…EGR1 was also represented by two probesets and the expression levels were significantly reduced after 16 h. This gene codes for a zinc-finger transcription factor. EGR proteins play central roles in controlling the differentiation program initiated by pre-TCR signalling [37,38] and in mature CD4 + T cells it was recently shown that EGR1 is required for CD154 (CD40 ligand) transcription [39]. The transcriptional regulators HEY1 and KLF10 are involved in regulation of cell fate decisions and proliferation, respectively, but have yet not been investigated in T lineage cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the DN cells expressed CD3 at a moderate or low level, although a CD3 Ϫ population was also identified which are likely to be even more immature. CD3 ϩ DN cells are likely to be either immature T cells or CD3 ϩ NK cells, while DP cells could represent a slightly later stage of immature T cell development (23). However, some DP cells, proposed to be activated T cells, are normally present in adults and are increased in adults with various autoimmune disorders (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that Egr-1 is also induced in T cells upon activation with PMA and IO. The role of Egr1 in T cells is less well defined; however, it has been suggested to act as a regulator of Fas ligand expression (49) and thymocyte development (50). Significantly, the Egr1 promoter is activated by T cell receptor agonist ligands (51), and Egr1 gene expression increases shortly after concanavalin-A stimulation of cultured T lymphocytes (52), observations that support a potential role for Egr1-mediated transcription of genes in activated T cells.…”
Section: Figmentioning
confidence: 99%